Analisis Pendapatan Usaha Dendeng Ikan Tuna Pada Industri Rumah Tangga Kub Kembang Baru Nangahure Kelurahan Wuring Kecamatan Alok Barat Kabupaten Sikka - Bernadeta Bela Bunga; Sarlina Noni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Tuna fish is one of the commodities that easily undergo decay therefore the household industry KUB Kembang Baru Nangahure does various kinds of processing including processing tuna into tuna jerky. The purpose of this study is to find out the income earned from tuna jerky business in the kub kembang baru nangahure household industry in KelurahanWuring, West Alok Subdistrict, Sikka Regency and also to find out the feasibility of tuna jerky business in KUB Kembang Baru Nangahure. Based on the results of research on the kub kembang baru nangahure household industry, it was concluded that the total cost of receipts obtained by KUB Kembang Baru was Rp. 6,250,000 and then the total production cost incurred amounted to Rp. 4,900,000, so that the total revenue is reduced by the total cost after processing income obtained by the kub kembang baru nangahure household industry that produces tuna jerky Rp. 1,350,000. Tuna jerky business in the household industry KUB Kembang Baru Nangahure seen from the Revenue Cost Ratio this business is worth trying because the value of R / C is greater than one which is 1.27